PEMANFAATAN LIMBAH KULIT BUAH KAKAO SEBAGAI PUPUK ORGANIK DI KECAMATAN LAMURU KABUPATEN BONE - Junaedi, Junaedi (Jurnal BALIRESO, 2017)
Community service activities such as extention, demonstration plots, training and mentoringrelated to the utilization of cocoa pods as compost had been implemented in the Lamuru District,Bone Regency. This activity aimed to improve the knowledge and skills of farmers related to theutilization of cocoa pods and in situ materials through appropriate technology for composting.Based on the results of training and mentoring that has been done, it can be seen that the farmershad been able to produce compost independently. In situ Materials used by farmers consists ofcocoa pod, straw, prunings cocoa and shade trees and manure.